Peningkatan Produktivitas Padi Gogo di Lahan Kering Masam melalui Aplikasi Pembenah Tanah Biochar Limbah Pertanian - Nurida, Neneng Laela; Jubaedah, Jubaedah; Dariah, A. (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
The opportunity to improve upland rice production on acid mineral soil is still high. However, the main problem of this soil is high soil acidity that inhibit crop growth, causing low production. The objective of this study was to evaluate the effects of agricultural waste biochar application on upland rice (Oryza sativa L.) productivity and improvement of acid mineral soil properties. The study was conducted at Agricultural Research Station of Tamanbogo, East Lampung on July-October 2013 (session 1), December 2013-April 2014 (session 2), May-August 2014 (session 3) and October 2014-February 2015 (session 4). The experimental design was split plot design, which the main plots were two types of biochar (cacao shell and rice husk), the sub plots were biochar rates (0; 5 t/ha and 15 t/ha) with five replications. The parameters measured were upland rice growth, yield and soil properties (Bulk density, soil pH and Al3+). The result showed that during the four planting seasons, the addition of cocoa shell biochar resulted better response on upland rice growth and yield compare to rice husk biochar, with crop yield of 2.54-3.97 t/ha dry grain. The dose of 5 and 15 t/ha biochar provided a stable yield and improvement of dry grain around 74.02-179.4% compare to no biochar addition for three consecutive sessions. The cocoa shell biochar applications showed better response on soil acidity (increase soil pH and reduce Al3+ ) and soil bulk density compared to rice husk. In degraded acid mineral soil, upland rice productivity and soil properties improvement can be increased by adding of 15 t/ha cacao shell biochar with a dose of 15 t / ha for getting dry grain more optimal.